EBV induces persistent NF-κB activation and contributes to survival of EBV-positive neoplastic T- or NK-cells - Takada, Honami (PLoS One, 2017)
Epstein–Barr virus (EBV) has been detected in several T- and NK-cell neoplasms such as extranodal NK/T-cell lymphoma nasal type, aggressive NK-cell leukemia, EBV-positive peripheral T-cell lymphoma, systemic EBV-positive T-cell lymphoma of childhood, and chronic active EBV infection (CAEBV). However, how this virus contributes to lymphomagenesis in T or NK cells remains largely unknown. Here, we examined NF-κB activation in EBV-positive T or NK cell lines, SNT8, SNT15, SNT16, SNK6, and primary EBV-positive and clonally proliferating T/NK cells obtained from the peripheral blood of patients with CAEBV. Western blotting, electrophoretic mobility shift assays, and immunofluorescent staining revealed persistent NF-κB activation in EBV-infected cell lines and primary cells from patients. Furthermore, we investigated the role of EBV in infected T cells. We performed an in vitro infection assay using MOLT4 cells infected with EBV. The infection directly induced NF-κB activation, promoted survival, and inhibited etoposide-induced apoptosis in MOLT4 cells. The luciferase assay suggested that LMP1 mediated NF-κB activation in MOLT4 cells. IMD-0354, a specific inhibitor of NF-κB that suppresses NF-κB activation in cell lines, inhibited cell survival and induced apoptosis. These results indicate that EBV induces NF-κB-mediated survival signals in T and NK cells, and therefore, may contribute to the lymphomagenesis of these cells.